Writing labour stone quarry workers in Delhi - Talib, Mohammad (Oxford University Press, 2010)
This book is the culmination of research over a period of 25 years. It highlights the relation between the rocks from which India's great capital city is constructed and the people who sacrifice to turn them into a useful form. The result is an interesting account of the lifeworld of some of the poorest and most forgotten people: the stone quarry workers. The book describes the material conditions of their poverty and exploitation as well as their aspirations and poetic expressions. It is a major contribution to the anthropology of labour in the informal sector of a globalized Indian economy and society. In producing a field study of a labour settlement barely thirty kilometres from the heart of Delhi, the urban mainstream society gets to see a world that lies beyond its boundaries. The workers are in themselves fragmentary and fortuitously organized around the themes of class and labour, who represent their consciousness by means of protest and conformity. Despite the workers' varying accounts of their personal lives, the narrative constructs labour in relation to wider society. Labour is intertwined with society in relations of necessity, contingency, reflexivity, and expediency.